Enterovirus 71 encephalomyelitis and Japanese encephalitis can be distinguished by topographic distribution of inflammation and specific intraneuronal detection of viral antigen and RNA - Wong, K.T.; Ng, K.Y.; Ong, K.C.; Ng, W.F; Shankar, S.K.; Mahadevan, A.; Radotra, B.; Su, I.J.; Lau, G.; Ling, A.E.; Chan, K.P.; Macorelles, P.; et al. (British Neuropathological Society, 2012)
Aims: To investigate if two important epidemic viral encephalitis in children, Enterovirus 71 (EV71)e ncephalomyelitis and Japanese encephalitis (JE) whose clinical and pathological features may be nonspecific and overlapping, could be distinguished.